THE NOTION OF EDUCATING FAITH VALUES IN THE NOVEL â€œAPI TAUHIDâ€ BY HABIBURRAHMAN EL SHIRAZY - Suparjo suparjo; Dwi Destiana (IAIN Purwokerto, 2015)
Abstract: Faith or creed education commonly called tauhid is the core of Islamic or tauhid is the soul of life. Along and technology, the development of globalization and ease human social interaction, becomes a kind of obscure threat of moslem faith today. As well as a double-edge knife, the development of technology, can provide benefit and harm. Moral degradation, westemized lifestyle, violence, free sex, and corruption are some other negative impacts. Even more, many radical idiologies with extreme idea. swhich can destroy solidarity for moslem to the other. Those are signs, which show what a bad faith in humanself. In this case, Islamic education has a role with the spirit of